Whole-body predictors of wrist shot accuracy in ice hockey: a kinematic analysis - Michaud-Paquette, Y.; Magee, P.; Pearsall, D.; Turcotte, R. (Sports Biomechanics, 2011)
The purpose of this study was to identify joint angular kinematics that corresponds to shooting accuracy in the stationary ice hockey wrist shot. Twenty-four subjects participated in this study, each performing 10 successful shots on four shooting targets. An eight-camera infra-red motion capture system (240 Hz), along with passive reflective markers, was used to record motion of the joints, hockey stick, and puck throughout the performance of the wrist shot. A multiple regression analysis was carried out to examine whole-body kinematic variables with accuracy scores as the dependent variable. Significant accuracy predictors were identified in the lower limbs, torso and upper limbs. Interpretation of the kinematics suggests that characteristics such as a better stability of the base of support, momentum cancellation, proper trunk orientation and a more dynamic control of the lead arm throughout the wrist shot movement are presented as predictors for the accuracy outcome. These findings are substantial as they not only provide a framework for further analysis of motor control strategies using tools for accurate projection of objects, but more tangibly they may provide a comprehensive evidence-based guide to coaches and athletes for planned training to improve performance.